2015
DOI: 10.1002/anie.201505147
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Responsive Pharmacological Chaperones for Rescuing Mutant Glycosidases

Abstract: A general approach is reported for the design of small-molecule competitive inhibitors of lysosomal glycosidases programmed to 1) promote correct folding of mutant enzymes at the endoplasmic reticulum, 2) facilitate trafficking, and 3) undergo dissociation and self-inactivation at the lysosome. The strategy is based on the incorporation of an orthoester segment into iminosugar conjugates to switch the nature of the aglycone moiety from hydrophobic to hydrophilic in the pH 7 to pH 5 window, which has a dramatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 37 publications
4
42
0
Order By: Relevance
“…The finding that PGRN acts as a co-chaperone of HSP70 and is required for disaggregation of GCase, together with the facts that chaperone-based treatments aiming to enhance GCase lysosomal localization have proven to be a promising alternative to enzyme replacement treatment (ERT) and substrate reduction therapy (SRT) for GD (Zimran et al, 2013, Sanchez-Fernandez et al, 2016, Jung et al, 2016, Mena-Barragan et al, 2015), and recombinant HSP70 has been shown to effectively correct altered lysosomal stability seen in Niemann–Pick B disease (NPD) (Kirkegaard et al, 2010), promoted us to examine whether PGRN would have therapeutic effects in GD. Indeed, we have found that recombinant PGRN protein is therapeutic against Gaucher disease (Jian et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The finding that PGRN acts as a co-chaperone of HSP70 and is required for disaggregation of GCase, together with the facts that chaperone-based treatments aiming to enhance GCase lysosomal localization have proven to be a promising alternative to enzyme replacement treatment (ERT) and substrate reduction therapy (SRT) for GD (Zimran et al, 2013, Sanchez-Fernandez et al, 2016, Jung et al, 2016, Mena-Barragan et al, 2015), and recombinant HSP70 has been shown to effectively correct altered lysosomal stability seen in Niemann–Pick B disease (NPD) (Kirkegaard et al, 2010), promoted us to examine whether PGRN would have therapeutic effects in GD. Indeed, we have found that recombinant PGRN protein is therapeutic against Gaucher disease (Jian et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Most of these molecules target the active site and must therefore be reversible inhibitors, ideally with shorter half-lives that the substrate, but compounds that interact with other regions of the protein could in principle also work. Recently, pH sensitive chaperones have been developed which bind strongly to the GCase active site at neutral pH but lose affinity when exposed to the lower pH found in the lysosome [25]. While some chaperones have reached human clinical trials, to date none has shown any significant improvement in clinical outcome.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…It would be useful to find molecules that bind and stabilize AGAL mutants when they are in the neutral environment of the endoplasmic reticulum, but dissociate when the protein reaches the lysosome. This point was specifically addressed incorporating an orthoester segment into DGJ [93]. …”
Section: Future Perspectives For Therapymentioning
confidence: 99%